2023
DOI: 10.1093/hmg/ddad007
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA sequencing reveals transcriptional changes of human choroidal and retinal pigment epithelium cells during fetal development, in healthy adult and intermediate age-related macular degeneration

Abstract: Age related macular degeneration (AMD) is the most prevalent cause of blindness in the developed world. Vision loss in the advanced stages of the disease is caused by atrophy of retinal photoreceptors, overlying retinal pigment epithelium (RPE) and choroidal endothelial cells (CECs). The molecular events that underline the development of these cell types from in utero to adult as well as the progression to intermediate and advanced stages AMD are not yet fully understood. We performed single cell RNA-Sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 68 publications
5
8
0
Order By: Relevance
“…Given the near-ubiquitous Emcn mRNA expression we observed in the mouse choroidal pericyte cluster, we were surprised that EMCN was absent from human pericytes within a previously published choroidal cell atlas, despite expression in choroidal fibroblasts that was similar to our observation in mouse (17). This finding was confirmed by exploring other published human datasets accessible via Spectacle (27), including data from Voigt et al 2022 and Collin et al, 2023 (28,29). Consistent with findings from our initial analysis, limited EMCN expression was detected in pericytes within these datasets, while fibroblast expression appeared widespread.…”
Section: Discussionsupporting
confidence: 82%
“…Given the near-ubiquitous Emcn mRNA expression we observed in the mouse choroidal pericyte cluster, we were surprised that EMCN was absent from human pericytes within a previously published choroidal cell atlas, despite expression in choroidal fibroblasts that was similar to our observation in mouse (17). This finding was confirmed by exploring other published human datasets accessible via Spectacle (27), including data from Voigt et al 2022 and Collin et al, 2023 (28,29). Consistent with findings from our initial analysis, limited EMCN expression was detected in pericytes within these datasets, while fibroblast expression appeared widespread.…”
Section: Discussionsupporting
confidence: 82%
“…The RPE dataset included >10,000 single nucleus transcriptomes from peripheral samples. Their transcriptomes generally resembled those reported in recent single cell studies (15,(17)(18)(19)(55)(56)(57), although our dataset is currently the largest. Along with known markers, we found several novel markers that are selectively expressed by RPE even when compared to all known ocular cell types (Fig.…”
Section: Pigmented Cellssupporting
confidence: 76%
“…They include WFDC1, CXCL14, and CALCB enriched in macular RPE, and PMEL and IGFBP5 enriched in peripheral RPE. Many of these genes were also reported to be differentially expressed in previous studies (15,(17)(18)(19)(55)(56)(57)(58).…”
Section: Pigmented Cellsmentioning
confidence: 57%
See 1 more Smart Citation
“…The presence of NLRP3 inflammasome in RPE cells has been debated in age-related macular degeneration research. Investigations of NLRP3 expression in single-cell human data for the RPE-choroid tissues show low expression of NLRP3 compared to macrophages [ 91 , 92 ]. In support of this finding, a study of human RPE cell lines found no mRNA, protein, or evidence of NLRP3 inflammasome activation in the RPE [ 93 ].…”
Section: Ocular Expression Of Tlrs and Nlrp3mentioning
confidence: 99%